Tools and frameworks for evaluating the implementation of learning health systems: a scoping review - Darren Rajit; Sandra Reeder; Alison Johnson; Joanne Enticott; Helena Teede (BMC, 2024)
Abstract Introduction Despite increased interest in learning health systems (LHS), a paucity of guidance and tools for evaluating LHS implementation exists. To address this, we aim to undertake a scoping review on existing tools and evaluation of exemplars of LHS implementation. Methods We conducted a scoping review of peer-reviewed studies within Scopus, EMBASE, MEDLINE, and MEDLINE in-process that described (1) the evaluation of the implementation of an operating LHS or (2) the development of a framework or tool to facilitate this evaluation. Anima, basic research, abstracts, non-English language articles, and publications before 2018 were excluded. All study designs were considered. Findings From 1300 studies initially identified, 4 were eligible, revealing three tools with nine implementation evaluation examples. The identified tools shared constructs which were evaluated, including: Stakeholders, Data, Research Evidence, Implementation, and Sociotechnical Infrastructure. However, there was divergence in evaluation methodology. Tools ranged from a five-point numerical rating system for process maturity with a radar chart called the Network Maturity Grid (NMG); the Kaiser Permanente Washington (KPWA) LHS Logic Model, which provides a broad list of constructs and sample measures relevant to LHS operations; and finally LADDERS, a simple tool or form-based template designed for consistent evaluation over time. The NMG tool was the most mature in terms of adaptation and adoption. Notably, two (NMG and the KPWA LHS Logic Model) out of three tools conceptualized the LHS as a suite of processes and devised tools were processes that linked these constructs. Implications for toolkit development The evaluation of LHS implementation remains an under explored area of investigation, as this scoping review found only three tools for LHS implementation evaluation. Our findings indicate a need for further empirical research in this area and suggest early consensus in constructs that need to be considered during evaluation.